2019
DOI: 10.3389/fmicb.2019.02654
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nutrients Drive Function and Composition of phoC-Harboring Bacterial Community in Acidic Soils of Southern China

Abstract: Phosphorus (P) deficiency is an important factor that limits the agricultural production potential in acidic soils. The bacterial phoC gene encodes non-specific acid phosphatase (ACP), which participates in the mineralization of soil organic P and is therefore important for the improvement of soil P availability. However, the function and community population of phoC-harboring bacteria and their driving factors in acidic soil remain largely unknown. For this study, 51 soil samples and 207 plant samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 62 publications
1
9
0
1
Order By: Relevance
“…It is widely recognized that soil pH has strong correlations with soil bacterial diversity (Li et al, ; Zhou, Guo, Chen, & Jia, ), which is the main driver of bacterial community diversity (Wei et al, ), and consistent results were also obtained in our study (Figure a; Table ). Furthermore, present study showed that soil bacterial community diversity existed positive correlations with soil nutrients, including total C, total N, total P, available P, available N, available K, and soluble Ca 2+ , which were similar with previous findings (Deng et al, ; Wang et al, ; Wei et al, ; Zheng, Wang, Li, Song, & Shen, ). It's worth mentioning that numerous studies have indicated the correlations between soil factors and fungal community diversity, such as soil pH (Zhang et al, ), P content (Burke, Carrino‐Kyker, & Burns, ), and C/N (Yang, Cheng, Dou, & An, ); however, no similar observations were obtained in present study.…”
Section: Discussionsupporting
confidence: 92%
“…It is widely recognized that soil pH has strong correlations with soil bacterial diversity (Li et al, ; Zhou, Guo, Chen, & Jia, ), which is the main driver of bacterial community diversity (Wei et al, ), and consistent results were also obtained in our study (Figure a; Table ). Furthermore, present study showed that soil bacterial community diversity existed positive correlations with soil nutrients, including total C, total N, total P, available P, available N, available K, and soluble Ca 2+ , which were similar with previous findings (Deng et al, ; Wang et al, ; Wei et al, ; Zheng, Wang, Li, Song, & Shen, ). It's worth mentioning that numerous studies have indicated the correlations between soil factors and fungal community diversity, such as soil pH (Zhang et al, ), P content (Burke, Carrino‐Kyker, & Burns, ), and C/N (Yang, Cheng, Dou, & An, ); however, no similar observations were obtained in present study.…”
Section: Discussionsupporting
confidence: 92%
“…total P) and stoichiometry (e.g. C:N, C:P, N:P) were found to be predictors of community diversity and composition or abundance of class A acid phosphatase communities (Luo et al 2019;Zheng et al 2019;Gaiero et al 2020). phoDharbouring communities may also respond uniquely to resource limitations and available P resources (Jorquera et al 2014;Margalef et al 2017;Gaiero et al 2020).…”
Section: Microbially-driven P Cyclingmentioning
confidence: 96%
“…Soil adhering to the roots of L. bicolor was shaken off and placed in plastic bags. The soil samples were stored at 4 • C. To measure rhizosphere soil pH, we used a pH meter (Mettler Toledo FE20, Shanghai, China) to analyze a soil-water suspension (soil: water, 1: 2.5) after shaking (Zheng et al, 2019). Available P was extracted by the ammonium fluoride method and analyzed by the molybdate blue method (Murphy and Riley, 1962).…”
Section: Soil Sampling Sitesmentioning
confidence: 99%